Interactive Participation-Based Premarital Class Model for Reproductive Health and Marital Age Maturity in Support of the ASTA CITA Program - Tri Sunarsih; Dwi Yulinda; Erydani Anggawijayanto; Rosdiana Rosdiana; Nendhi Wahyunia Utami; Endah Puji Astuti; Elvika Fit Ari Shanti; Ekawati Ekawati (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Early marriage and divorce remain persistent public health and social concerns in Indonesia, contributing to poor reproductive health outcomes and hindering human resource development. While premarital education programs exist, their modeled association in delaying marriage age and improving reproductive health is still uncertain. These challenges highlight the need for more engaging, evidence-based interventions that address not only knowledge gaps but also family dynamics, cultural norms, and participants’ readiness to adopt healthier marital and reproductive practices. This study aimed to design and empirically examine an interactive premarital class model by modeling participation as a mediating mechanism linking premarital education with reproductive health and marital age maturity within the ASTA CITA program. Method: A cross-sectional survey was conducted from March to August 2025 at the Kulonprogo Religious Affairs Office, Yogyakarta. A total of 260 prospective brides and grooms were recruited using purposive sampling. Data were collected through a validated questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Results: Predisposing factors (knowledge, attitudes, and beliefs) (?=0.552; p<0.001) and reinforcing factors (family support and policy) (?=0.391; p<0.001) significantly increased participation. Participation showed a strong statistical association with reproductive health (?=0.763; p<0.001) and marital age maturity (?=0.789; p<0.001). The model showed strong explanatory power (R²=0.805 for participation; R²=0.582 for reproductive health; R²=0.622 for marital age maturity) and high predictive relevance (Q²>0.35). Conclusion: The interactive premarital class model showed robust modeled associations between participation, reproductive health literacy, and marital age maturity. This participatory, family- and community-based approach may inform the development of premarital education strategies in similar institutional contexts, particularly in efforts to address early marriage and reproductive health challenges. However, given the cross-sectional design and single-site setting, these findings should be interpreted as exploratory, and broader implementation would require further validation through longitudinal or multi-site studies across diverse institutional and socio-cultural settings. Future research is needed to assess long-term outcomes and contextual adaptability.